Preparation of fish collagen and vancomycin microspheres based on microfluidic technology and its application in osteomyelitis - Hu, Xiaowu; Tang, Jinshan; Yu, Huaixi; Yang, Hanshi; Lu, Xiaoqing; Zheng, Donghui (Frontiers in Bioengineering and Biotechnology, 2023)
At present, the clinical treatment of osteomyelitis and osteomyelitis-induced bone defects is challenging, easy to recur, drug toxic side effects, secondary or multiple surgeries, etc. The design of biodegradable composite biomaterials to improve antibiotics in the local precise anti-infection at the same time to complete the repair of bone defects is the current research hot spot. Herein, a composite hydrogel with a double bond at the end (FA-MA) was prepared by affinity addition reaction between fish collagen (FA) and methacrylic anhydride (MA) under photoinitiator initiation conditions, then, FA-MA was amino-activated by EDC/NHC, and vancomycin was attached to FA-MA via amide bonding to prepare FA-MA-Van hydrogels, and finally, the composite hydrogel microspheres were prepared by microfluidic technology. The structure of the hydrogel was confirmed by SEM (elemental analysis), optical microscopy, FTIR, and XPS to confirm the successful preparation. The composite hydrogel microspheres showed the better antimicrobial effect of hydrogel microspheres by bacterial coated plate experiments and SEM morphology results, with the antimicrobial class reaching 99.8%. The results of immunofluorescence staining and X-ray experiments showed that the hydrogel microspheres had a better effect on promoting bone repair. This engineered design of hydrogel microspheres provides clinical significance for treating osteomyelitis at a later stage.